The influence of zirconium carbide addition on oxidation behaviour of NiAl coatings prepared by cold spraying of ball-milled Ni–Al alloy powder. (1st September 2013) - Xie, R; Li, D; Yang, G; Li, C
Abstract : The microstructure and oxidation behaviour of NiAl and NiAl/ZrC coatings prepared by cold spraying of ball-milled Ni/Al alloy powders were investigated. The microstructure of the mechanically alloying Ni/Al powder and NiAl coating was characterised by scanning electron microscopy and X-ray diffraction analysis. The results show that the homogeneity of the microstructure of ball-milled Ni/Al composite powder was modified by the addition of fine ZrC particles. The microstructure of the cold sprayed NiAl/ZrC coatings was denser than that of the NiAl coatings without the addition of ZrC particles. α -Al2 O3 oxide scales were formed on the surface of both NiAl coating and NiAl/ZrC coatings during oxidation at 1050°C. After NiAl with ZrC addition was oxidised at 1130°C for 50 h, the α -Al2 O3 scale was less than 5 μm, which exhibited excellent oxidation resistance.